THE IMPACT OF OBJECT-BASED ATTITUDE TOWARDS BEHAVIOR BELIEF AND BEHAVIOR ATTITUDE ON THE USE OF HALODOC APPLICATION - Eva Riani; Ardi Ardi (Jurnal Ekonomi, 2023)
This research aims to investigate factors affecting people's intention to use the Halodoc application. The sample in this research was gathered with a purposive sampling method with inclusion criteria of people using the Halodoc application with a minimum age of 18. Data was gathered using a questionnaire that was spread online using Google Form. The questionnaire consists of 32 questions using Likert Scale 1-5. There are 101 respondents participating in this study. Data were then statistically analyzed using the PLS-SEM method with SmartPLS 4.0.9.1 application. The result of this research states that user satisfaction as the component of object-based attitude significantly affects perceived usefulness and perceived ease as the component of behavior belief. Perceived usefulness and perceived ease of use also affect behavior attitude significantly. This research also states that perceived ease of use can directly affect intention to use significantly without going through mediating variables. But, perceived usefulness does not significantly affect the intention to use through a direct path without using a mediating variable (behavior attitude).